2019
DOI: 10.1021/acs.jpca.9b01992
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Isomerizations by Rotation around C–C or C–N Bonds: A Comparative Study on Matrix-Isolated Glycolamide and N-Hydroxyurea Excited with Near-IR Laser Light

Abstract: Conformers and near-IR-induced conformational transformations were studied for monomers of glycolamide isolated in low-temperature matrixes. Two conformational isomers of the compound, Tt and Cc, were trapped from the gas phase into solid Ar matrixes. Selective near-IR excitation of glycolamide molecules adopting the Tt form led to the Tt → Cc conformational conversion. Analogously, selective near-IR excitation of Cc conformers resulted in the Cc → Tt transformation. Monochromatic near-IR light, generated by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…S5, ESI †). The identification of Tt and Cc conformers of GAm is unequivocal, not only due to the excellent agreement between the experimental and computed IR spectra but also based on the comparison with previous data for these two conformers isolated in argon matrices 31 (Tables S6 and S7, ESI †). Interestingly, we found that the Tt -Cc conformational isomerization induced upon excitation at the second OH stretching overtone is site-selective.…”
Section: Vibrational Excitation Of 3n(oh)supporting
confidence: 66%
See 3 more Smart Citations
“…S5, ESI †). The identification of Tt and Cc conformers of GAm is unequivocal, not only due to the excellent agreement between the experimental and computed IR spectra but also based on the comparison with previous data for these two conformers isolated in argon matrices 31 (Tables S6 and S7, ESI †). Interestingly, we found that the Tt -Cc conformational isomerization induced upon excitation at the second OH stretching overtone is site-selective.…”
Section: Vibrational Excitation Of 3n(oh)supporting
confidence: 66%
“…They are simple molecules where vibrational excitations to the first OH stretching overtone produce stable high-energy conformers under cryogenic conditions. [29][30][31] High-energy conformers of simple carboxylic acids such as formic and acetic acids are known to decay fast (few minutes or less) by tunneling. 1,7 Moreover, HA, GAc and GAm have strong infrared absorptions in the fundamental OH stretching and welldefined first OH stretching overtone absorptions, measured under matrix-isolation conditions, which suggests the possibility to detect experimental bands due to their second OH stretching overtones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations